Differences in Current Hookah and Cigarette Smoking Status Attitudes and Beliefs at a Florida University: A Discriminant Analysis - Gail Castañeda; Tracey E. Barnett; Sergio Romero; Mi Jung Lee; Jann MacInnes (University of North Florida, 2019)
Rising college hookah use, in the absence of cigarettes, suggests attitudinal differences among both forms of tobacco consumption. This study examines which smoking attitudes/beliefs are most distinguishing across current non-smokers, cigarette smokers, hookah smokers, and dual (cigarette and hookah-only) smokers at a Florida university. Self- administered questionnaire data from 373 university students were categorized into four groups based on self-reported 30-day smoking status. Discriminant analysis was used to examine maximal differences between groups across perceived peer acceptability of cigarette smoking, peer acceptability of hookah smoking, hookah smoking harmfulness, and attitude toward peer hookah smoking. Descriptive analyses indicated an overall awareness of hookah smoking harmfulness across all four groups. Discriminant analysis findings indicated peer acceptability of cigarette smoking (r = .75) contributed the most to attitude/belief differences across all four groups. Pairwise group comparisons showed a significant attitudinal mean difference in peer acceptability to cigarettes for cigarette smokers vs hookah smokers (T=3.9, p=.001). Study findings underscore the need for campus-based anti-smoking social norm approaches targeting positive hookah smoking peer use attitudes. Programming efforts are recommended to implement the use of self-reported perceived peer acceptability to cigarette smoking as a potential risk indicator for students at-risk for cigarette or dual use.